Public Perception On Aedes Albopictus Mosquitoes, Fitness Cost To Insecticides Exposure And Its Activity Pattern In Penang Residential Areas - Aminodin, Sumayyah (2017)
A study was carried on Aedes albopictus mosquito in residential areas and its fitness cost in response to the insecticide exposure. The study to evaluate the current knowledge level on Aedes mosquitoes and dengue among Penang residence in urban Sg. Dua and sub-urban Batu Maung involved 202 respondents mainly on the observation of general Aedes' mosquito behaviour and its preventive measure, and lifestyle (on usage of artificial light) in changing the behaviour of Aedes mosquitoes. There is a direct link between the knowledge of the Aedes biting frequency with human lifestyle on the light use. However, the level of knowledge is poor on Aedes mosquitoes and dengue in both urban and sub-urban respondents.